Book review: Anil Kumar Vaddiraju, Urban Governance and Local Democracy in South India. Issue 2 (December 2022) - Kenoth, Rajesh
Anil Kumar Vaddiraju, Urban Governance and Local Democracy in South India . Routledge, 2021, 112 pp., ₹695. ISBN: 9781032045795 (Paperback).